Characterizing the scouring efficiency of Granular Activated Carbon (GAC) particles in membrane fouling mitigation via wavelet decomposition of accelerometer signals - Wang, Jingwei (2017)
Particle fluidization is a promising unsteady-state shear means of mitigating membrane fouling, thereby potentially lower the energy requirement in membrane-based water treatment processes. In particular, the particles facilitate back-transport in the polarization layer and also play the role of mechanical scouring agents, the latter of which is dominant for millimeter-sized particles. In this study, the scouring efficacy of three Granular Activated Carbon (GAC) particle diameters (namely, 1.20 mm, 1.85 mm, and 2.18 mm) has been investigated using an accelerometer to reveal the fluid dynamics. Specifically, because both liquid and solid phases contribute to the accelerometer signal, wavelet decomposition was used to extract information in the higher-frequency detail signals that reflect the particle dynamics. The energy contained in the accelerometer signal indicative of the solid phase dynamics correlated well with the extent of fouling mitigation in the filtration tests; the liquid contribution was less significant when the GAC particles were fully fluidized. Results indicate that the smallest particle diameter of 1.20 mm conferred the least scouring efficiency, while both the larger particle diameters of 1.85 mm and 2.18 mm provided similar scouring efficiency. Calculations of energy requirement indicate that the energy requirement of all three particle diameters (dp) were similar at lower scouring efficiency, whereas the energy requirement of the smallest dp of 1.20 mm was the greatest at higher scouring efficiency. Optimization of the particle diameter hinges on the balance between particle inertia, and the difference between superficial liquid velocity and minimum fluidization velocity.